Design Of Mobile Stock Management Application Integrated with Application Programming Interface: Case Study on One of The SMEs In Bandung - initasari, Gita; Retnowaty, Agung Tri; Subagja, Roni Ilham; Ramlan, Isak; Widaretna, Titi (Informatics Management, Engineering and Information System Journal, 2024)
Rapid Application Development (RAD) is a software development methodology prioritizes speed and flexibility. This study uses this approach to design and develop a web-based augmented reality furniture marketing information system by integrating a popularity-based ranking model in D FURNITURE. The RAD method was chosen because it can accelerate the software development process through an iterative cycle involving users in every development stage. This development cycle includes four phases: needs analysis, design, development, and implementation. The first stage is needs analysis, which collects data through interviews and surveys with D FURNITURE management and potential system users. This process aims to identify users' primary needs and preferences, including augmented reality visualization features and popularity-based ranking mechanisms. The data obtained becomes the basis for compiling the specifications of the system to be developed. The second stage is design, where an initial prototype of the system is developed based on the results of the needs analysis. This prototype includes the user interface design, augmented reality technology integration, and a popularity-based ranking algorithm. Users then test this prototype to obtain feedback on functionality and user experience. The third stage is development, where the designed system is developed into a fully functional version. At this stage, the development team refines the prototype based on the feedback provided during the design stage. Testing is carried out periodically to ensure that each system component works according to specifications and user needs. The final stage is implementation, which integrates the system into the D-FURNITURE operational environment. At this stage, end users receive training to ensure they can utilize all system features optimally. In addition, the integrated ordering system via WhatsApp media is also tested to ensure smooth communication between customers and the company. Using the RAD method, this study succeeded in developing a marketing information system that is responsive, adaptive, and responsive to user needs. The iterative development cycle ensures that the resulting system is technically efficient and provides an optimal user experience.